Kryptoracemates - Tiekink, Edward R. T. * (Springer Nature, 2020)
Racemic crystals normally crystallise in centrosymmetric spacegroups containing equal numbers of enantiomers. More rarely, racemates may crystallise in non-centrosymmetric space-groups having glide symmetry or, even more rarely, in space-groups devoid of a centre of inversion, having no rotary-inversion axes nor glide plane. The latter class of crystals form the subject of the present bibliographic review – a survey of kryptoracemic behaviour. The term kryptoracemic alludes to the presence of a hidden or non-crystallographic centre of inversion between two molecules that might otherwise be expected to crystallise in an achiral space-group, often about a centre of inversion. Herein, examples of molecules with stereogenic centres crystallising in one of the 65 Sohncke space-groups are described. Genuine kryptoracemates, i.e. crystals comprising only enantiomorphous pairs are described followed by an overview of non-genuine kryptoracemates whereby the crystal also contains other species such as solvent and/or counterions. A full range, i.e. one to six, stereogenic centres are noted in genuine kryptoracemates. Examples will also be described whereby there are more that one enantiomeric pair of molecules in the crystallographic asymmetric unit. A more diverse range of examples are available for non-genuine kryptoracemates. There are unbalanced species where in addition to the enantiomeric pair of molecules, there is another enantiomeric molecule present. There are examples of genuine co-crystals, solvated species and of salts. Finally, special examples will be highlighted where the counterions are chiral and where they are disparate, both circumstances promoting kryptoracemic behaviour.